Optimalisasi SIPD dan SPIP dalam Meningkatkan Kualitas Laporan Keuangan: Pentingnya Kompetensi SDM - Naida, Nasrun (Solusi, 2024)
This study aims to describe the implementation of Local Government Information Systems (LGIS), Government Internal Control Systems (GICS), and Financial Report Quality (FRQ); evaluate the effect of LGIS and GICS implementation on FRQ; and analyze the role of Human Resource Competence in moderating the relationship between LGIS and GICS on FRQ. The research employs a quantitative approach, focusing on theory testing through numerical variables and data analysis using statistical procedures. The study utilizes the Partial Least Square (PLS) method in Structural Equation Modeling (SEM) with the WarpPLS 8.0 software, involving 128 respondents from various Local Government Agencies. The results indicate that the implementation of LGIS and GICS positively and significantly affects FRQ. Furthermore, Human Resource Competence enhances the relationship between LGIS and GICS with FRQ, suggesting that improving HR competence can increase the effectiveness of LGIS and GICS implementation in enhancing financial report quality. This study is expected to provide input and contribute to the District Government as an evaluation tool for the implementation of LGIS and GICS. This study also combines the variables of LGIS and GICS on FRQ using the Agency Theory approach.